Analysis of The Stochastic Model of Epidemic Malaria Transmission With Discrete Time Markov Chain in Gedebgie, Ethiopia - Belay, Zemenu; Wassie, Aman (International Journal on Orange Technologies, 2025)
Malaria is an infectious disease caused by the Plasmodium parasite and transmitted between humans through bites of female Anopheles mosquitoes. This thesis modifies the SIR model to predict the spread of malaria in Gedebgie using the data from Gedebgie health station. A stochastic model describes the dynamics of malaria and human population compartments in terms of stochastic and deterministic equations and these equations represent the relations between relevant properties of the compartments. The aim of the study is to understand the important parameters in the transmission and spread of epidemic malaria disease. Our results show that the reproduction number R0, is less than 1, so that the disease dies out and the probability of an outbreak is zero. Numerical simulations have been carried out applying the numerical software Matlab and python. These simulations show the behavior of the infected population in time. From the analysis and discussions of the model, SIR model is a good model to study the spread of malaria in Gedebgie.